Pemberdayaan Kelompok Masyarakat Desa Curug, Kecamatan Gunung Sindur, Bogor dalam Mewujudkan Desa Edutainment - Kusumajanti Kusumajanti; Asep Kamaluddin Nashir; Ni Putu Eka Widiastuti (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
Curug Village, Gunung Sindur District, Bogor is geographically in the middle of an industrial environment. The diverse profiles of the people in Curug Village have encouraged the Curug Village Head to optimize his environmental resources. The Curug Village Government wants to empower the environment and its people so that their Regional Original Income can increase. Departing from the aspirations of the people and government officials of Curug Village to have a tourist area that has an impact on increasing people's income and regional original income. PPDM in Curug Village as a form of implementation of research results related to. Optimization of groups in the community that are in accordance with the urgency of the needs of the Curug Village community. The PPDM team provides solutions to the problems of the Curug Village community who want to increase community income with a holistic approach based on research in the fields of Communication, Negotiation and Diplomacy, and Finance, as well as BUMDes. Thus it is hoped that by using the formation assistance approach, empowering groups based on the economy, tourism, by utilizing the resources of Curug Village in the form of land which is the location for Edutainment Tourism. Diverse human resources are an added value for providing assistance so that the community has independence and is able to accelerate village development in the areas of goat/sheep livestock, rabbit farming, fish farming, ornamental plant cultivation, processing of fish products, and self-employment. The final results in the first year are expected that Curug Village can have an agreement for an edutainment-based science-techno-park model.